2021
DOI: 10.3390/app11114760
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulfinate-Enriched Allium sativum Extract as an Adjunct to Antibiotic Treatment of Sepsis in a Rat Peritonitis Model

Abstract: Up to now, there are no studies that have shown a decrease in morbidity and mortality in the context of sepsis and septic shock, except for antibiotic therapy and the objective-guided resuscitation strategy. The goal was to evaluate the use of thiosulfinate-enriched Allium sativum extract (TASE) as an adjuvant in the management of sepsis. An experimental in vivo study was carried out with male Sprague Dawley® rats. Animals were randomized in three treatment groups: the control group (I), antibiotic (ceftriaxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Regarding weight status, rats infused with TASE not only did not show a significant drop in body weight but their body mass increased more quickly in the TASE + BGE group, highlighting that TASE can reduce the impact of an infection/inoculum, as previously described [ 23 ].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Regarding weight status, rats infused with TASE not only did not show a significant drop in body weight but their body mass increased more quickly in the TASE + BGE group, highlighting that TASE can reduce the impact of an infection/inoculum, as previously described [ 23 ].…”
Section: Discussionsupporting
confidence: 62%
“…Looking for the immunomodulatory capacity of compounds derived from garlic, this study has been designed using two extracts (TASE and BGE) and its combination with antibiotic, finding a decrease in TNF-alpha in the first 24 h in the two groups where BGE was included. In a previous work [ 23 ], we compared only TASE to antibiotic treatment in T3 and T7, and we did not find a significant decrease in TNF-alpha. In the present work, we also found no differences in any of the cytokines analyzed at T5 (i.e., 120 h later), which falls within the context of regulation of the host inflammatory response, where toxins are eliminated or neutralized 24 h after contact [ 36 ].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…To evaluate the efficacy in the sepsis-induced management, clinical, analytical, microbiological and histopathological parameters were evaluated in the control group, in the group treated with antibiotic, and in the group treated with antibiotic plus Allium sativum extract. The results confirmed that the utilization of Allium sativum extract as an adjuvant to antibiotic treatment in the management of sepsis could improve the sepsis attenuation, ameliorating clinical parameters of rats as weight, ocular secretions, whiskers separation and physical activity level, inhibiting Escherichia coli proliferation and thus, reducing overall mortality after an animal peritonitis model [8].…”
supporting
confidence: 63%